Reformulasi Pertanggungjawaban Pidana Fraud Pada Lembaga Investasi Negara - Aisyah Nurhalizah; Handoyo Prasetyo (Universitas Semarang, 2025)
This study analyzes the differences in the legal frameworks for fraud prevention in state investment institutions in Indonesia and Singapore to formulate an ideal model for strengthening Danantara's accountability as a state investment institution. The normative gap arises because Indonesia does not yet have an integrated legal system capable of addressing non-budgetary corporate fraud, while Singapore implements a more comprehensive approach through the PCA, Penal Code, and SFA, which are operated in an integrated manner by the CPIB, MAS, and CAD. This study uses a normative juridical method with legislative, comparative, and conceptual approaches to assess the effectiveness of regulations and formulate a reconstruction of the authority of law enforcement agencies. The results show that the limited definition of corruption in the Corruption Eradication Law and the scope of the Corruption Eradication Commission's authority, which is limited by Article 11, create a jurisdictional gap in handling fraud at Danantara. In contrast, Singapore has succeeded in establishing an integrated and preventive legal system based on the principle of corporate accountability. The novelty of this study lies in the idea of ​​reformulating the KPK's authority to cover strategic corporate fraud and harmonizing criminal law and state investment governance within a single supervisory framework. These findings have important implications for the formulation of national policies to strengthen the integrity of state investment institutions through adaptive and prevention-oriented law enforcement. Penelitian ini menganalisis perbedaan kerangka hukum pencegahan fraud pada lembaga investasi negara di Indonesia dan Singapura untuk merumuskan model ideal penguatan akuntabilitas Danantara sebagai lembaga investasi negara. Kesenjangan normatif muncul karena Indonesia belum memiliki sistem hukum terintegrasi yang mampu menjangkau fraud korporasi non-anggaran, sementara Singapura menerapkan pendekatan yang lebih komprehensif melalui PCA, Penal Code, dan SFA yang dioperasikan secara terpadu oleh CPIB, MAS, dan CAD. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, perbandingan, dan konseptual untuk menilai efektivitas pengaturan dan merumuskan rekonstruksi kewenangan lembaga penegak hukum. Hasil penelitian menunjukkan bahwa keterbatasan definisi korupsi dalam UU Tipikor serta ruang lingkup kewenangan KPK yang dibatasi Pasal 11 menimbulkan jurisdictional gap dalam penanganan fraud di Danantara. Sebaliknya, Singapura berhasil membangun sistem hukum yang terintegrasi dan preventif berdasarkan prinsip akuntabilitas korporasi. Kebaruan penelitian ini terletak pada gagasan reformulasi kewenangan KPK untuk mencakup fraud korporasi strategis serta harmonisasi hukum pidana dan tata kelola investasi negara dalam satu kerangka pengawasan. Temuan ini memberikan implikasi penting bagi perumusan kebijakan nasional guna memperkuat integritas lembaga investasi negara melalui penegakan hukum yang adaptif dan berorientasi pada pencegahan.